ANALISIS KEBERLANJUTAN PENGELOLAAN HUTAN LINDUNG MANGROVE DI BATU AMPAR, KABUPATEN KUBU RAYA, PROVINSI KALIMANTAN BARAT. - Endang Karlina; Cecep Kusmana; Marimin Marimin; M Bismark (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2016)
Mangrove protection forest has functions and benefits, in economic, ecological, and social. Its management requires planning to ensure the sustainability ofits functions and benefits. This study aimed to observe the sustainability level ofthe mangrove protection forest management planning in Batu Ampar and to determine the factors that affect the sustainability management of mangrove protection forest. Data was analyzed by using RAP-MPforest with multidimensional scaling method. The results showed that sustainability status was sustainable enough on the ecological criteria (54.59%); less sustainable on the economic criteria (34.06%) as well as social criteria (42.03). The factors that affected on the sustainability status ofmangrove protection forests namely: (1) establishment offorest area boundaries; (2) suitability of area allotment; (3) availability of mangrove seedlings; (4) protection offlora and fauna; (5) government revenue from management and utilization; (6) income level ofcommunity; (7) effective resolution mechanisms ofland conflicts; and (8) local cultural practices in preservation; (9) availability ofcommunity organizations and (10) community involvement in the management ofthe forest. Management planning that does not consider these factors in a balance manner would not guarantee the sustainability of management of mangrove protection forest in Batu Ampar.